2009
DOI: 10.1007/s11250-009-9499-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of drug resistance among enterococci and Salmonella from poultry and cattle in Ethiopia

Abstract: Enterococci and Salmonella were isolated from feces of chicken in intensive poultry farms and cattle which are maintained following traditional practices. Their resistance to different antibiotics was also determined. A total of 298 enterococcal isolates consisting of Enterococcus faecium (49.6%), Enterococcus durans (26.9%), Enterococcus hirea (11.9%), and Enterococcus faecalis (11.5%) were obtained. Among the enterococci, resistance to erythromycin (Ery), clindamicin (Cli), amoxicillin (Amo), ampicillin (Amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
(24 reference statements)
5
19
1
Order By: Relevance
“…This variation might be due to difference in the study population where most of the clients in the present study had habit of animal contact and this was supported by Bekele and Ashenafi, reported as 100% VRE Enterococci isolated from faeces of chicken and cattle in Ethiopia [20]. Comparison of colonization of VRE among HIV positives (7.8%) and HIV negative (3.1%) clients’ revealed that there was a slightly higher VRE in HIV positive patients.…”
Section: Discussionsupporting
confidence: 56%
“…This variation might be due to difference in the study population where most of the clients in the present study had habit of animal contact and this was supported by Bekele and Ashenafi, reported as 100% VRE Enterococci isolated from faeces of chicken and cattle in Ethiopia [20]. Comparison of colonization of VRE among HIV positives (7.8%) and HIV negative (3.1%) clients’ revealed that there was a slightly higher VRE in HIV positive patients.…”
Section: Discussionsupporting
confidence: 56%
“…Previously, high resistance to erythromycin in broiler Salmonella isolates was reported by Bekele and Ashenafi (3), who similarly had detected high resistance results for penicillin G, doxycycline hydrochloride in parallel to our findings. Also, the resistance rates determined in this study for the chicken isolates were in agreement with previous reports for tetracycline (5,12), oxytetracycline (10), ciprofloxacin and enrofloxacin (5), enrofloxacin and penicillin G (14), cephalexin and cephazolin (3), streptomycin and ampicillin (3,5,12), amoxycillin/clavulanic acid (3), and ceftiofur (10). The resistance rate observed in the broiler isolates for sulphamethoxazole/trimethoprim 19:1 was relatively lower than previously reported by Ishihara et al (10) in chicken isolates.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, there are several reports on Salmonella isolates that are resistant to several antimicrobial agents (Multi Drug Resistant -MDR) both in the developed and developing countries from chicken meat (4,15,17,18,21,22,23), and from chickens (3,5,7,10,12). The emergence of these MDR Salmonella has significant outcomes for the safety of the food supply, namely chicken meat, directly as a source of MDR Salmonella, and indirectly as a reservoir of antimicrobial genetic elements that can be exchanged between intestinal bacteria (2).…”
Section: Introductionmentioning
confidence: 99%
“…The minimum required sample size was calculated based on an expected prevalence of 15.4% [23] with 95% desired confidence interval and 5% absolute precision using the formula described in Thrusfield et al [29]. Accordingly, 270 chickens (100 from BPMC, 90 from HPMC and 80 from Hawassa commercial farm) were sampled.…”
Section: Methodsmentioning
confidence: 99%
“…The limited studies have reported the presence of multidrug resistant Salmonella strains in chicken farms [22, 23], which cannot be killed by antimicrobials and hence increase the morbidity, mortality and costs associated disease. Overall, studies conducted on Salmonella in Ethiopia are scarce.…”
Section: Introductionmentioning
confidence: 99%